M.N. Hoyt correspondence - Hoyt, M. N.
ALS (1861 December 21; Camp Griffin, Va.) from Hoyt discussing fighting under General George Brinton McClellan. Includes a typewritten transcript of the letter.
Union Army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: McClellan, George Brinton, -- 1826-1885.; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Soldiers